Desempenho de espécies arbóreas nativas do sul do Brasil em sistema agroflorestal - Farias Perez, Julio Cesar (2022)
The most widespread model of intensive industrial agricultural production in the world has been shown to be unsustainable and cannot be maintained any more. One of the contradictions of this model in southern of Brazil is the destruction of the tree component in agroecosystems, because the most agricultural crops is benefit for the presence of pollinators, natural enemies or another ecosystem services that come from nearby native vegetation. It is possible to bring back the tree component in agroecosystems through the implementation of Agroforestry Systems (SAF) and if native tree species are used, it would also promote the conservation of biodiversity in addition to promoting synergies and ecosystem processes responsible for greater stability and resilience of the system. The objective of this work was to investigate the silvicultural behavior of 26 tree species native to the Atlantic Forest implanted in SAF and to verify their impact on some ecological indicators such as soil quality and ecological succession six years after its implantation. Based on the results of this work, the ten species recommended for implementation in SAF in the southern region of Brazil are wild smoked smoke, timbauva, toucan, Azorean horse, mastic, tapir bark, dry flour, purple ipe, guarita and cedar; being the first five pioneers and the last five secondary, respectively. After 6 years of implementation of the SAF, the soil has low compaction, the pH remains close to 4.5, and essential nutrients such as phosphorus, potassium, calcium and magnesium are found in adequate concentrations according to the Paraná state fertilization manual. Above ground, a similar amount of litter accumulated as in areas of natural forest fragments (10 t/ha). The diversity of the vegetal naturally regeneration was 1.3 in the Shannon index (H´) and the main orders in the epiedaphic fauna are springtails, ants, beetles besides spiders and mites, with diversity (H´) of 0.7. The implementation of SAF in Paraná means an alternative that reconciles the greatest tree coverage in this region largely affected by deforestation.